Genotoxic potential of nanomaterials: in vitro evaluation of iron oxide nanoparticles - Valdiglesias, Vanessa (2016)
The rapidly growing industrial and medica! use of nanomaterials, particularly metal oxide nanoparticles, has led to growing concern about their toxicity. Moreover, human beings are commonly exposed to their potential harmful effects since these nanomaterials are frequently present in a number of industrial products of very regular use. Among them, iron oxide nanoparticles (ION) have been widely used in various biomedical applications, for both diagnosis and therapy, due to their unique magnetic properties.